2017
DOI: 10.1001/jamaoto.2017.2019
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Prevalence and Prognostic Value of Perineural Invasion and Angiolymphatic Invasion in Human Papillomavirus–Positive Oropharyngeal Carcinoma

Abstract: IMPORTANCE Recently, the American Joint Committee on Cancer (AJCC) updated its staging system for human papillomavirus (HPV)–positive oropharyngeal squamous cell carcinoma (OPSCC). The prognostic significance of perineural invasion (PNI) and angiolymphatic invasion (ALI) within this staging system is unknown. OBJECTIVE To examine the prevalence and prognostic significance of PNI and ALI in HPV-positive OPSCC. DESIGN, SETTING, AND PARTICIPANTS A retrospective review was performed of all patients with HPV-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Factors like immune surveillance of virus-specific tumor antigens, like high CD8þ T-cell infiltration, and lack of field cancerization may contribute to the better treatment outcome of HPV-positive OPSCC's overall survival and prognosis [36][37][38][39]. Further, one study found that HPV-positive tumors were not correlated with perineural invasion (PNI) or perivascular invasion (PVI), which have been reported as independent predictors of poor survival [40]. It was also found that HPV-driven tumors display a cohesive invasion pattern at the leading edge of the tumor [41].…”
Section: Discussionmentioning
confidence: 99%
“…Factors like immune surveillance of virus-specific tumor antigens, like high CD8þ T-cell infiltration, and lack of field cancerization may contribute to the better treatment outcome of HPV-positive OPSCC's overall survival and prognosis [36][37][38][39]. Further, one study found that HPV-positive tumors were not correlated with perineural invasion (PNI) or perivascular invasion (PVI), which have been reported as independent predictors of poor survival [40]. It was also found that HPV-driven tumors display a cohesive invasion pattern at the leading edge of the tumor [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results should be validated in independent data sets to determine if there is a difference in rates of lo- coregional or distant relapse. Third, there are several unmeasured variables including perineural invasion [28] and previous tobacco smoking history [2], which may be relevant to determining the risk of death in HPV+ OPSCC. Further, factors such as the chemotherapy regimen and quality of RT cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Although mechanisms of HPV1 and HPV-negative (HPV2) HNSCC are different, 7 both tumor entities show an invasive phenotype 8,9 and metastasis into the neck lymph nodes (LNs) and distant sites. [10][11][12] Thus, despite their distinct genetic nature 13 and clinico-pathological appearance, 14 treatment approaches of HPV2 and HPV1 HNSCCs are essentially the same and include surgery, radiotherapy, or chemoradiotherapy (cRT) as single or combination modalities, depending on the location and stage of the tumor.…”
mentioning
confidence: 99%